Usefulness of a clinical risk score to predict the response to cardiac resynchronization therapy. (1st June 2018) - Providencia, Rui; Marijon, Eloi; Barra, Sergio; Reitan, Christian; Breitenstein, Alexander; Defaye, Pascal; Papageorgiou, Nikolaos; Duehmke, Rudolph; Winnik, Stephan; Ang, Richard; Klug, Didier; Gras, Daniel; et al.
Abstract: Background: Almost 1/3 of heart failure patients fail to respond to cardiac resynchronization therapy (CRT). A simple clinical score to predict who these patients are at the moment of referral or at time of implant may be of importance for early optimization of their management. Methods: Observational study. A risk score was derived from factors associated to CRT response. The derivation cohort was composed of 1301 patients implanted with a CRT defibrillator in a multi-center French cohort-study. External validation of this score and assessment of its association with CRT response and all-cause mortality and/or heart transplant was performed in 1959 CRT patients implanted in 4 high-volume European centers. Results: Independent predictors of CRT response in the derivation cohort were: female gender (OR = 2.08, 95% CI 1.26–3.45), NYHA class ≤ III (OR = 2.71, 95% CI 1.63–4.52), left ventricular ejection fraction ≥ 25% (OR = 1.75, 95% CI 1.27–2.41), QRS duration ≥ 150 ms (OR = 1.70, 95% CI 1.25–2.30) and estimated glomerular filtration rate ≥ 60 mL/min (OR = 2.01, 95% CI 1.48–2.72). Each was assigned 1 point. External validation showed good calibration (Hosmer–Lemeshow test- P = 0.95), accuracy (Brier score = 0.19) and discrimination (c-statistic = 0.67), with CRT response increasing progressively from 37.5% in patients with a score of 0 to 91.9% among those with score of 5 (Gamma for trend = 0.44, P < 0.001). Similar results were observed regarding all-cause mortality or heart transplant. Conclusion: The ScREEN score (S ex c ategory, R enal function, E CG/QRS width, E jection fraction and N YHA class) is composed of widely validated, easy to obtain predictors of CRT response, and predicts CRT response and overall mortality. It should be helpful in facilitating early consideration of alternative therapies for predicted non-responders to CRT therapy. Highlights: A clinical risk score for CRT response and prognostication is proposed. Female gender, eGFR ≥ 60 mL/min, LVEF ≥ 25%, QRS ≥ 150 ms and NYHA I-III constitute the ScREEN score. Derivation in a multicentre nationwide registry and validation in 4 high volume centers is presented.